Back to Basics: Autologous Tissue: 1.5www.aornjournal.org/content/cme. (29th August 2018) - Spruce, Lisa
Abstract: Perioperative personnel manage autologous tissue when they care for patients undergoing procedures requiring the use of bone, soft tissue, or other autologous tissue to repair or replace defects. Use of autologous tissue can minimize the risk of rejection, disease transfer, and infection compared with the use of artificial materials. There are important steps to follow when handling autologous tissue to ensure it is safe for replantation and does not become contaminated. This Back to Basics article provides strategies for managing some types of autologous tissue, including bone flaps, parathyroid tissue, skin grafts, and veins. Tissue management strategies include creating strict documentation policies, standardizing processes and communication, and implementing routine audits to assess compliance.